Medical Students’ Knowledge about Tuberculosis (Journal of Fatima Jinnah Medical University, 2018)
Background: Tuberculosis (TB) has been declared a global emergency. As Pakistan ranks 6th among the countries with highest TB burden, this disease presents an immense challenge to the health infrastructure. So the aim of this study was to assess the knowledge regarding Tuberculosis among medical students.Methodology: A cross sectional survey was conducted among 2nd, 3rd, and 4th year students of Fatima Jinnah Medical College. This was an anonymous survey and participation was voluntary. Sample was selected using systematic random sampling technique and self administered structured questionnaires were used for data collection. Data entry and analysis were performed using SPSS.Results: A total of 221 students participated in the study. Majority of the students (97%) were well informed about the causative organism and the most common site of involvement of TB. Seventy five percent were able to correctly identify the most common mode of transmission of this disease, whereas only a small percentage (29%) had knowledge of the age group most commonly affected by tuberculosis. There was a poor level of understanding regarding diagnostic techniques, and only 20% correctly mentioned the treatment duration for TB. Only 36% of students were aware of MDR-TB, and 65% knew about the availability of TB vaccine. The knowledge regarding free treatment for tuberculosis and the chest clinics set up by the government was not very encouraging, 56% and 50%, respectively. Only 31% of the students showed trust in public sector medical facilities for the treatment of TB.Conclusion: This study demonstrated a satisfactory elementary knowledge regarding TB among medical students, but there is a need to improve the understanding regarding diagnostic procedures and treatment guidelines. For effective control of TB, immediate action to improve undergraduate medical education is essential, with special emphasis on national guidelines.